Pengaruh Pupuk Urea dan Mineral Zeolit terhadap Emisi Karbondioksida (Co2) pada Pertanaman Padi (Oryza Sativa L.) di Tanah Gambut - Muh Bambang Prayitno; Hendri Dunand; Dwi Probowati Sulistyani (Seminar Nasional Lahan Suboptimal, 2019)
Prayitno MB, Dunand H, Sulistyani DP. 2019. The influence of urea fertilizer and zeolite minerals on carbon dioxide (Co2) emissions on the rice plant (Oryza Sativa L.) in peat soil. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 437-444. Palembang: Unsri Press. This study aims to determine the effect of nitrogen and zeolite fertilization on CO2 emissions in paddy rice plantation in peat soils. The study was conducted in the greenhouse of the Faculty of Agriculture, Sriwijaya University, Inderalaya, South Sumatra Province, from September to December 2018. The results of this study indicate that the treatment of nitrogen fertilizer produces the highest CO2 emissions in the production phase of the U3 treatment (average emissions: 3.80 mg/plant/day) and the lowest emissions in the vegetative phase (age 55 days) on the U2 treatment (average emissions: 2.41 mg/plant/day). The zeolite treatment produced the highest CO2 emissions in the production phase of Z1 treatment (average emission: 3.82 mg/plant/day) and the lowest emissions in the generative phase (age 65 days) on treatment Z1 (average emission: 2.43 mg/plant/day). The highest CO2 emission from the combination of nitrogen and zeolite fertilizers is in the rice production phase U2Z3 (3.95 mg/plant/day) and the lowest CO2 emission at 55 days on treatment U2Z1 (2.22 mg/plant/day).Keywords: peat soils, CO2 emissions, paddy rice, urea fertilizer, zeolite minerals